IMPLEMENTASI PENGGUNAAN MEDIA PEMBELAJARAN AUGMENTED REALITY DALAM TEMA 9 MENJELAJAHI RUANG ANGKASA DI SD NEGERI 3 JAMBU - Putri Ica Apriliani; Fina Fakhriyah; Sekar Dwi Ardianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This research is motivated by the low ability to understand concepts which causes students' learning outcomes in Science and Indonesian to be standard with KKM scores. So it is necessary to do research with the aim of knowing the difference in the average pretest posttest score, increasing the learning outcomes of class VI students at SD Negeri 3 Jambu, and the effectiveness of implementing Augmented Reality learning media in thematic learning theme 9 exploring space sub-theme 1 amazing regularity. Augmented Reality is a technology that combines 2D and 3D virtual objects into a real 3D environment and then projects these virtual objects in real time. This study used a quantitative experimental approach which was carried out in class VI of SD Negeri 3 Jambu. The population of this research is all students of class VI. The sampling technique for this study used a purposive random sampling technique. The method used in this study was pre-experimental with the one group pretest posttest design. Data collection techniques include interviews, questionnaires, documentation, observation, and tests. The instruments used were written tests in the form of multiple choice and descriptions to measure how far the learning outcomes were obtained by students and questionnaires to capture student response data in the use of Augmented Reality learning media. Data analysis used paired sample t-test, N-Gain test, independent sample t-test.